2017
DOI: 10.3126/jngmc.v13i1.16398
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution as a Risk Factor of Acute Lower Respiratory Tract Infection in Children

Abstract: Introduction: This study was conducted to find out if indoor air pollution has any risk in occurrence of acute lower respiratory tract infection (ALRI) in children. Materials and methods: It was a case control study conducted on total 214 children 107 cases and 107 controls fulfilling the inclusion criteria with age and sex matched. Detailed history and physical examination was done after taking informed consent. History of upper respiratory tract infection in the family members and siblings, history of smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The research has identified various environmental factors that pose a risk for Acute Lower Respiratory Infection (ALRI). These factors include the utilization of wood as a cooking fuel, the presence of domestic animals, the absence of a separate kitchen, a family history of smoking, the lack of windows, and the use of kerosene lamps as a source of light (147). Nevertheless, the study on the UCC IAQ management program was unsuccessful in significantly reducing its effect on the lower respiratory system.…”
Section: Chapter V Discussion and Conclusion Discussionmentioning
confidence: 99%
“…The research has identified various environmental factors that pose a risk for Acute Lower Respiratory Infection (ALRI). These factors include the utilization of wood as a cooking fuel, the presence of domestic animals, the absence of a separate kitchen, a family history of smoking, the lack of windows, and the use of kerosene lamps as a source of light (147). Nevertheless, the study on the UCC IAQ management program was unsuccessful in significantly reducing its effect on the lower respiratory system.…”
Section: Chapter V Discussion and Conclusion Discussionmentioning
confidence: 99%